MONITORING OF THE AQUATIC ENVIRONMENT OF AN INDUSTRIAL AREA WITH MULTIPLE SOURCES OF POLLUTION - PIETRUCIN, DOROTA (Bulletin of Geography. Physical Geography Series, 2013)
Chemical plants are important objects of hydrogeological research, due to their potentially large impact on the soil and water environment. The topic of this paper is one of the oldest chemical plants in northern Poland, owned by the ‘Zachem’ company and located in the city of Bydgoszcz. The plant is located on a 500 ha property. This area has isolated about a dozen landfills for different types of wastes. In order to make a proper estimation of the influence of a chemical plant on its environment we must first identify the geological and hydrogeological conditions, and also the character of its land-use. Field investigations must be preceded by in-depth historical studies of the plant’s development and the technologies used within, and an identification of historical and present contamination sources. The author describes the current condition of the plant’s groundwater monitoring and indicates the direction of modernization and further development. This paper presents the problems faced when designing a groundwater monitoring network for industrial areas.